Climate variability, the proliferation and expansion of major livestock diseases in East Gojjam, Northwestern Ethiopia. (2017) - Ayal, Desalegn Yayeh; Woldetisadik, Muluneh; Kassa, Tesfu; Tilahun, Getachew; Filho, Walter Leal
This study explores the link between climate variability and its effect on livestock production and system. Mixed research method was used to explore and explain the problem. Data were collected from both primary and secondary sources. The results of the study show that farmers have perceived an increase in temperature and the erratic behaviour of rainfall in its onset, cessation and intensity over time. The study reveals tick and tick borne diseases, trypanosomiasis and epidemics of infectious diseases such as anthrax and blackleg occurred frequently. Deterioration of pasture, diseases and resource scarcity are major constraints for livestock development. Livestock are kept for drafting, manure, milk, meat, packing, means of income and transportation. Multifunctional of the sector is complemented with other livelihoods and used to diversify their economic interest and open access to informal loan. Thus, the sector acts as insurance against shocks.